One-pot three-component synthesis of quinoxaline and phenazine ring systems using Fischer carbene complexes - Roy, Priyabrata; Ghorai, Binay Krishna (Beilstein Journal of Organic Chemistry, 2010)
One-pot three-component coupling of o-alkynylheteroaryl carbonyl derivatives with Fischer carbene complexes and dienophiles leading to the synthesis of quinoxaline and phenazine ring systems has been investigated. This involves the generation of furo[3,4-b]pyrazine and furo[3,4-b]quinoxaline as transient intermediates, which were trapped with Diels–Alder dienophiles. This is the first report on furo[3,4-b]pyrazine intermediates.
Keywords: azaisobenzofuran; Diels–Alder; Fischer carbene complex; phenazine; quinoxaline